Shared decision-making in physical therapy: a cross-sectional observational study. (2nd November 2021) - Hausheer, Andrea Claudia; Suter, Larissa Carolina; Kool, Jan
Abstract: Background: The objectives of this study were to evaluate physical therapists' shared-decision-making behaviour in a rehabilitation centre and a private practice, to determine agreement between patients' preferred levels of involvement in shared-decision-making and therapists' assumptions of patients' preferences, and to examine predictors of shared-decision-making behaviour. Methods: Thirty initial physical therapy consultations were audio-recorded. Shared-decision-making behaviour was observed using the observing patient involvement (OPTION) instrument. A pre-defined threshold of ≥35/100 points was considered to represent good shared-decision-making behaviour. The Control Preferences Scale was used to measure patients' preferred levels of involvement in shared-decision-making and therapists' assumptions. Shared-decision-making behaviour was analysed using descriptive statistics. Predictors of shared-decision-making behaviour were analysed by multiple regression. Results: Shared-decision-making OPTION ratings were a median of 50.5/100 (25th, 75th percentiles 44.0, 66.0). Agreement between patients and physical therapists regarding shared-decision-making was poor (weighted kappa −0.26 (95% confidence interval −0.51 to −0.01). Therapy settings, education and the interaction of education and work experience predicted shared-decision-making behaviour ( b = 15.76, p < 0.001; b = 8.05, p < 0.05; b = −0.33, p < 0.05). Conclusion: Shared-decision-making behaviour was good, and predicted by therapy setting, education and the interaction of education with work experience. Because of the limited number of institutions and therapists with MSc or PhD qualifications in this study, further research is required into the relationship between education and communication skills.